Rekognisi MBKM bentuk free form dalam riset tematik pemanfaatan lahan oleh masyarakat di Pulau Mansinam: MBKM Free Form Activities and Thematic Research on Community Land Use on Mansinam Island - Bernadetta Sadsoeitoeboen; Jenny Raweyai; Max Tokede; Francina Kesaulija; George Mentansan; Zulfikar Mardiyadi (IGKOJEI: Jurnal Pengabdian Masyarakat, 2023)
As the flagship program of the Ministry of Culture, Higher Education, research and Technology through the Freedom to Learn the Independent Campus (MBKM) policy where students are required to master and be ready for the increasingly rapid development of science and technology. The free form MBKM activities carried out by the Faculty of Forestry UNIPA in 2022 are centered on Mansinam Island, the UNIPA campus and the Planning and GIS Laboratory of the UNIPA Faculty of Forestry involving parties outside the campus who come from the support of the Indonesia Mapping Community (IMC). The participants, which consisted of 9 students from the Faculty of Forestry UNIPA Bachelor of Forestry Study Program, were required to be able to develop science and technology that had a direct impact on the community, especially in honing hard and soft skills in using mapping/GIS applications and technology and being directly involved with the community. The purpose of this activity is to document the stages of the free front MBKM process and research on participatory mapping activities in compiling a land openness map on Mansinam Island. The results of the documentation of the free form MBKM activities of the Faculty of Forestry, UNIPA in 2022: include activities (i) Classroom learning, (ii) Learning in the form of work practices/Professional internships, (iii) Learning in the form of research, and (iv) Learning in the form of community service society can run well and successfully. The results of learning activities in the form of research produce a map of the distribution of open land covering an area of 300,244.56 m2 or 7.4% of the total area of Mansinam Island. Several administrative obstacles need to be fixed, but it is hoped that the 2023 MBKM program for the Faculty of Forestry will become the flagship MBKM program at the University of Papua and can be attended by all students in Indonesia. Key words: MBKM; Recognition; Thematic research; UNIPA